Professores iniciantes de educação física: discussões a partir das fontes de autoeficácia docente - Costa Filho, Roraima Alves da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The early period of teaching career is pointed as a critic period in teachers’ professional development. It influences, among other factors, teachers’ knowledge, conceptions and beliefs about teaching. In the field of Physical Education, studies on this theme are incipient. However, they suggest that the context in which classes take place makes the early career more challenging since the skills, competencies and beliefs of beginning teachers are in development. Thus, understanding how the situations experienced during this period can influence novice teachers, especially physical education teachers, can contribute to the formation of more confident teachers to teach in school, because their teaching practices are based on a set of values, beliefs and attitudes that seem appropriate and constituted throughout their lives. The teachers’ self-efficacy is one among these beliefs. Such belief perform a predictive and mediational role between the teachers’ thought and action and consists of four sources: enactive mastery experience, vicarious experience, social persuasion and physiological and affective states. Teacher self-efficacy refers to the judgement that teachers make regarding to their own capacity to teach, even to the most difficult students. This belief have been widely studied in different countries but remain relatively unexamined within physical education beginning teachers, especially in the Brazilian context. Therefore, this research aimed: a) to identify teaching experiences related to the capacity of teaching that were significant to novice teachers; b) to describe the circumstances in which these experiences occur; and c) to explore, based on the collected information, elements that can allow us to analyse them through the lens of the referential sources of self-efficacy. The participants were five novice Physical Education High School teachers who teach at different cities of the Board of Education of Limeira, SP...

O início da carreira docente é apontado como um momento crítico no desenvolvimento profissional dos professores, influenciando, dentre outros fatores, seus saberes, concepções e crenças sobre o ensino. No campo da Educação Física, estudos nessa temática são incipientes. Apontam que o contexto em que as aulas ocorrem podem tornar os desafios mais evidentes para os iniciantes, afetando-os de diversas maneiras. Desse modo, entender como as situações vividas nesse período influenciam o professor iniciante, em especial o de Educação Física, pode contribuir para a formação de docentes mais confiantes para ensinar na Educação Básica pois, ao lecionar, os professores o fazem a partir de um conjunto de valores, crenças e atitudes que lhes parece adequado e que foi constituído ao longo de suas vidas. Dentre essas crenças, apresenta-se a de autoeficácia docente, que exerce papel preditivo e mediacional entre o pensamento e a ação do professor e é constituída por quatro fontes: experiência direta, experiência vicária, persuasão social e estados fisiológicos e afetivos. Apesar de estudos internacionais apontarem as contribuições desse referencial para o comportamento do professor, no Brasil, são incipientes e escassos esses estudos, ainda mais considerando o contexto do professor iniciante de Educação Física. Desse modo, a presente pesquisa teve por objetivo: a) Identificar as experiências de ensino ligadas à capacidade de ensinar e que foram significativas para os professores iniciantes; b) Descrever em que circunstâncias essas experiências ocorrem; e c) Explorar, a partir dessas informações, elementos que nos permitam analisá-las à luz do referencial das fontes de autoeficácia. Participaram desta pesquisa cinco professores de Educação Física do Ensino Médio em início de carreira, que lecionam na região da Diretoria de Ensino de Limeira, SP. Esta é uma pesquisa exploratória de caráter qualitativo....
Keywords: Physical education and training - Study and teaching; Educação física - Estudo e ensino; Professores de educação fisica; Auto-eficácia; Prática profissional